2016
DOI: 10.1097/mib.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Ultrasonography in the Management of Crohnʼs Disease. A Review with Recommendations of an International Panel of Experts

Abstract: Bowel US is a tool for evaluation of CD lesions in terms of complications, postoperative recurrence, and monitoring response to medical therapy; it reliably detects postoperative recurrence and complications, as well as offers the possibility of monitoring disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 92 publications
4
89
1
5
Order By: Relevance
“…US is a noninvasive, radiation‐free, and inexpensive modality compared with CT, MRI, and endoscopy . Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity . A recent meta‐analysis showed that US has a high diagnostic accuracy for detecting CD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US is a noninvasive, radiation‐free, and inexpensive modality compared with CT, MRI, and endoscopy . Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity . A recent meta‐analysis showed that US has a high diagnostic accuracy for detecting CD .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity. 13,26 A recent meta-analysis showed that US has a high diagnostic accuracy for detecting CD. 8 The sensitivity and specificity of intestinal US in assessment of CD activity by evaluating intestinal wall inflammation were 85% and 91%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The global sensitivity of intestinal US for the primary diagnosis of CD has been assessed within many meta-analyses, showing a good diagnostic accuracy. In one of these meta-analyses [50], intestinal US showed sensitivity of 79.7% and specificity of 96.7% in diagnosing patients with suspected CD and detected ileal CD with sensitivity and specificity of 92.7% and 88.2%, respectively, and colonic CD with 81.8% sensitivity and 95.3% specificity. The conclusion is that US has better accuracy for proximal lesions [50].…”
Section: Crohn's Diseasementioning
confidence: 99%
“…In one of these meta-analyses [50], intestinal US showed sensitivity of 79.7% and specificity of 96.7% in diagnosing patients with suspected CD and detected ileal CD with sensitivity and specificity of 92.7% and 88.2%, respectively, and colonic CD with 81.8% sensitivity and 95.3% specificity. The conclusion is that US has better accuracy for proximal lesions [50]. Another research on patients with suspected CD, which used colonoscopy and MRI as comparative investigations, showed a high diagnostic value of intestinal US, having a sensitivity of 94%, a specificity of 97%, positive predictive value (PPV) 97%, and negative predictive value (NPV) 94% [51].…”
Section: Crohn's Diseasementioning
confidence: 99%
“…On the other hand, non-hepatic indications for CEUS include the management of IBD (estimation of disease activity, distinction between fibrous and inflammatory strictures, characterisation of suspected abscesses or to confirm and follow the route of fistulas) or pancreatic diseases (to characterise pancreatic focal lesions or to depict necrotic areas in the context of acute pancreatitis) [43, 50, 51, 53, 54, 63-65]. …”
Section: The Role For Us In Gastroenterologymentioning
confidence: 99%